Numerical damage identification of structures by observability techniques based on static loading tests. Issue 9 (1st September 2016) - Nogal, Maria; Lozano-Galant, Jose Antonio; Turmo, Jose; Castillo, Enrique
Abstract: This article proposes the application of the observability techniques to deal with damage detection in bridges from their structural response under static loading tests. Unlike previous works based on a symbolic approach to this technique, this article presents its first numerical application. With this aim, a novel algorithm is presented, which reduces the unavoidable numerical errors produced by the lack of precision of computers. To achieve an adequate accuracy in estimations, this numerical algorithm is complemented with another method to define the proper geometry of the corresponding finite element model. The comparison of the observability technique with other existing methods presented in the literature shows that the number of required measurements is significantly lower. Furthermore, contrary to other analysed methods, no information from the undamaged structure is required. The accuracy in estimations provided by the proposed method is very high as the differences with actual values are lower than 1%.